Kulturarvsstudier i en föränderlig värld - Magnusson, Gert; Nolin, Catharina (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2013)
The Department of Art History at Stockholm University is since 2009 head of a multidisciplinary Master’s programme in Cultural heritage management. The programme is dealing with cultural heritage in a legal and social planning process, global perspectives, theoretical studies and practical work, internship, master’s thesis. The students are trained in protection and developing the cultural heritage for the modern society as well as in national and international fields of work.